2011
DOI: 10.1111/j.1442-2042.2011.02906.x
|View full text |Cite
|
Sign up to set email alerts
|

Cruciferous vegetables intake and risk of prostate cancer: A meta‐analysis

Abstract: Abbreviations & Acronyms BMI = body mass index CI = confidence interval GSTM1 = glutathione S-transferases M1 OR = odds ratio PEITC = phenethyl isothiocyanate RR = relative risks Objective: To evaluate the relationship between cruciferous vegetables intake and risk of prostate cancer. Methods: A systematic literature search up to June 2011 was carried out in PubMed , and the references of retrieved articles were screened. The summary relative risks with 95% confidence interval for the highest versus the lowest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
92
1
2

Year Published

2011
2011
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 127 publications
(99 citation statements)
references
References 28 publications
4
92
1
2
Order By: Relevance
“…Organosulfur compounds found abundantly in cruciferous vegetables may also play a role. Isothiocyanates are organosulfur compounds that have been extensively researched for their anticancer properties 14, 54, 55, 56. However, accumulating evidence suggests sulforaphane, a compound within the isothiocyanate group, may have beneficial effects on vascular damage via the blockade of oxidative stress and/or inhibition of advanced glycation end products 57, 58.…”
Section: Discussionmentioning
confidence: 99%
“…Organosulfur compounds found abundantly in cruciferous vegetables may also play a role. Isothiocyanates are organosulfur compounds that have been extensively researched for their anticancer properties 14, 54, 55, 56. However, accumulating evidence suggests sulforaphane, a compound within the isothiocyanate group, may have beneficial effects on vascular damage via the blockade of oxidative stress and/or inhibition of advanced glycation end products 57, 58.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies suggest that consumption of vegetables and fruit are associated with a lower risk of developing prostate cancer (Liu et al, 2012;Zhou et al, 2013). Askari et al (2014) conducted a case-control study to evaluate the association between consumption of vegetables and fruit and prostate cancer.…”
Section: Protective Factorsmentioning
confidence: 99%
“…It is accepted that age, race/ethnicity and family history of prostate cancer are the only well established risk factors for the disease (American Cancer Society, 2011;Hoffman, 2011;Mori et al, 2011;Schröder, 2011). However, diet pattern and some variants were reported to be associated with altered risk of prostate cancer: Lin Yan (Yan et al, 2009) found consumption of soy foods could reduce prostate cancer risk and such protection may be associated with the type and quantity of soy foods; Ben Liu (Liu et al, 2012) between cruciferous vegetables intake and decreased risk of prostate cancer. As a common and major nutrient from daily vegetables, folate was believed to decrease risk of many cancer types, such as colon cancer, esophageal squamous cell carcinoma, esophageal adenocarcinoma and pancreatic cancer (Larsson et al, 2006;Kim et al, 2010), however, meta-analysis of six randomized controlled trials indicated association between a 24% increased risk of prostate cancer with folic acid intake (Wien et al, 2012).…”
Section: Introductionmentioning
confidence: 99%